The Conservation Status of the Barbary Macaque (Macaca sylvanus) in Algeria: Population Estimates and Human Impacts - Mourad Boumenir; Fany Brotcorne; Jean-Luc Hornick; Mokrane Iguer-Ouada; Nassim Moula (Animals, 2025)
The Barbary macaque (Macaca sylvanus), the only African macaque and an endangered species, faces significant conservation challenges. By compiling both published and unpublished data, this review aims to provide a comprehensive synthesis of the current state of knowledge on the Barbary macaque in Algeria, with a specific focus on (1) geographic distribution and population estimates, and (2) anthropogenic threats. We reviewed 409 studies and identified 41 relevant to the Algerian context. Our findings update population estimates, revealing over 9000 individuals across national parks such as Djurdjura, Gouraya, and Chréa. We also document new presence data of the species in Skikda and Jijel. Finally, an analysis of the available studies on the impact of anthropogenic activities on the species in Algeria shows that the primary factors affecting macaques include habitat loss, overgrazing, illegal trade, road mortality, and tourism-related disease transmission. While species monitoring has improved, many forest regions remain understudied. We call for expanded systematic research and conservation efforts, particularly in unsurveyed habitats such as the Akfadou and Guerrouche forests and Babors-Tababort National Park. By integrating diverse data sources, this review supports the need for evidence-based conservation of M. sylvanus in Algeria and highlights its critical role in North African biodiversity.